“Menggunting Pita” (Membangun Generasi Unggul Tanpa Stunting dengan Pola Hidup Bersih dan Sehat) di Desa Janapria - Lita, Bq Fitria Frisma; Halimatunnisa, Maulin; Pa’ni, D. Mustamu Qamal; Muqarrobin, Aoladul; Wahyudi, Iwan; Rukmana, Baiq Fitrihan (Jurnal Abdimas Kesehatan (JAK), 2025)
West Nusa Tenggara (NTB) Province ranks 4th highest nationally with a stunting rate of 32.7% higher than the national achievement percentage of 21.6%, where Central Lombok ranks highest for stunting incidence on a provincial scale in NTB Province Based on the explanation above, we are interested in carrying out community service activities with the theme of building a superior generation without stunting with a clean and healthy lifestyle for pregnant women and mothers with toddlers at one of the posyandu in Janapria Village, Central Lombok. This service activity aims to increase public knowledge and awareness regarding the importance of a clean and healthy lifestyle as an effort to prevent stunting in children. The method used is providing health education with evaluation using pretest and posttest on 31 mothers. The activity was carried out in one meeting involving health center officers and posyandu cadres. Health education activities carried out emphasize healthy patterns in providing good nutritious food for children by paying attention to hygiene patterns in preparing food such as washing food ingredients before cooking, washing hands before preparing food, regularly going to the integrated health post, paying attention to house cleanliness and sanitation. The pretest results showed that 49.7% of mothers had poor knowledge and after being given health education, mothers' knowledge increased by 81.6% which was included in the good knowledge category. This shows that health education is an effective intervention to increase knowledge.